A Precious Catalyst: Rhodium‐Catalyzed Formic Acid Dehydrogenation in Water. Issue 18 (30th April 2019) - Fink, Cornel; Laurenczy, Gábor
Abstract : The performance of rhodium complex [Cp*Rh(bis(pyrazol‐1‐yl)methane)Cl]Cl was evaluated for formic acid dehydrogenation in aqueous solution. Solid‐state X‐ray diffraction helped to confirm the catalyst structure. Multinuclear NMR spectroscopy was employed to follow the dehydrogenation of formic acid. The reactions have been carried out in high‐pressure NMR sapphire tubes. An activation energy of +77.19 ± 4 kJ/mol was determined via an Arrhenius plot, which is in good agreement with literature findings. The catalyst afforded a TOF of 1086 h –1 and exhibited good stability. Based on our observations and literature, we propose a catalytic cycle. Abstract : A novel rhodium catalyst, [Cp*Rh(bis(pyrazol‐1‐yl)methane)Cl]Cl, was studied to evaluate its suitability for formic acid dehydrogenation in aqueous solution. The crystal structure was investigated via X‐ray diffraction and various NMR spectroscopic methods were employed to ascertain relevant parameters in catalysis. We observed a TOF of 1086 h – 1 and estimated an activation parameter of +77.19 kJ/mol.